Fuzzy matching scheme for stereo vision based electronic travel aid - Balakrishnan, G.; Sainarayanan, G.; Nagarajan, R.; Sazali, Yaacob (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org